EFEKTIVITAS MEDIA AUDIOVISUAL BERBASIS LAGU CANDY NCT DREAM TERHADAP PELAFALAN KOSAKATA BAHASA ARAB SISWA KELAS IV MI NEGERI 5 JAKARTA UTARA: EFFECTIVENESS OF AUDIOVISUAL MEDIA BASED ON NCT DREAM'S CANDY SONG ON ARABIC VOCABULARY PRONUNCIATION OF GRADE IV STUDENTS OF MI NEGERI 5 NORTH JAKARTA - shofira maharani; Retno Purnama Irawati; Zaim Elmubarok (Universitas Negeri Semarang, 2025)
Learning Arabic now tends to utilize various media as tools to enhance the effectiveness of the learning process. One of the media that is currently popular among young people is KPOP songs. The use of audiovisual media based on songs as a medium for learning Arabic has become the focus of research to enhance the effectiveness of learning. With the presence of audiovisual media based on songs, it can refer to the interests and development of the fourth-grade students at MI Negeri 5 North Jakarta who have not yet achieved the learning objectives in speaking skills. Therefore, a fun and appropriate method is needed so that students do not get bored and tired in class. The objective of this research is to determine the effectiveness of implementing audiovisual media based on the song